Sound predictions in an urban context. Issue 1 (March 2022) - Niesten, J; Tenpierik, MJ; Krimm, J
Recent studies show that environmental noise in urban environments continues to be a great health risk. This noise is especially further transmitted by the hard materials that are mostly used for façades. To predict these effects it is desirable to have a reliable prediction method. There are already several ways to predict sound levels in an urban context. This paper investigates two while focusing specifically on a practical approach to show that the methods are suitable to use during an actual design project. The impact of changing a façade at a specific location is investigated using both prediction methods. A façade which reflects sound to a location where it has a smaller impact, a sound absorbing façade, and a façade which combines both are taken into consideration. These façade adaptions have the potential to improve the sound levels in the investigated area from 1.7 up to 9.3 dB(A).